Radiation cooling and heat conducting polyether-ether-ketone composite material as well as preparation method and application thereof

By melting and hot pressing the modified boron nitride with aramid fiber balls and polyether ether ketone powder, HO-BN&ANF/PEEK composite material was prepared, which solved the shortcomings of the existing composite material in terms of expansion, material selectivity and thermal conductivity, achieved excellent radiation cooling and thermal conductivity, and improved its performance and efficiency in a variety of application scenarios.

CN119570228AActive Publication Date: 2025-03-07JILIN UNIVERSITY

Patent Information

Application Number
CN202411821083.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-07
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing radiation-cooled composite materials have poor expansion, insufficient material selectivity, difficulty in using under single application scenarios and harsh conditions, and their thermal conductivity is insufficient to effectively improve passive cooling efficiency.

Method used

A preparation method is adopted to modify the boron nitride after high temperature calcination, and combine aramid fiber balls and polyether ether ketone powder for melting and hot pressing to form a HO-BN&ANF/PEEK composite material to improve its radiation cooling and thermal conductivity.

Benefits of technology

It has achieved excellent radiation cooling and thermal conductivity of composite materials, improved its application potential and utilization value, and showed good performance in military aviation, construction, energy and electronic packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570228A_ABST
    Figure CN119570228A_ABST
Patent Text Reader

Abstract

The invention provides a radiation cooling and heat conducting polyether-ether-ketone composite material and a preparation method and application thereof.The preparation method of the composite material comprises the specific steps that S1, boron nitride is subjected to high-temperature calcination and furnace cooling, and hydroxyl modified boron nitride is obtained; s2, dispersing aramid staple fibers in a poor solvent, and performing high-speed shearing to form microspheres, namely aramid fiber balls; s3, uniformly mixing the aramid fiber balls obtained in S2 with polyether-ether-ketone powder, then adding the hydroxyl modified boron nitride obtained in S1, and continuously and uniformly mixing to obtain a composite material dispersion; and S4, carrying out melting and hot pressing on the composite material dispersion obtained in S3 to obtain the target polyether-ether-ketone composite material. The preparation method of the material disclosed by the invention is simple, and the prepared polyether-ether-ketone composite material shows excellent radiation cooling performance, heat-conducting property and heat stability and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a radiation cooling and heat conducting polyetheretherketone composite material and a preparation method and application thereof. Background Art

[0002] As global warming and greenhouse effect continue to intensify, people use air conditioners, fans and other cooling equipment more and more frequently, resulting in a large amount of energy consumption. Passive daytime radiation cooling technology with zero energy consumption has attracted extensive research.

[0003] Patent CN118421115A discloses a passive radiation cooling coating, which not only has vivid colors, but also the photonic structure formed by the dense accumulation of the coating is conducive to the passive radiation cooling of the material. Patent CN118727269A discloses a radiation cooling composite film with good mechanical properties, optical properties, hydrophobicity and thermal stability. However, there are still many problems in the current research on radiation cooling composite materials, such as poor scalability, insufficient material selectivity, single application scenario and difficulty in use under harsh conditions.

[0004] As a special engineering plastic, polyetheretherketone has excellent structural stability and infrared emission capabilities, and has great application potential in the field of radiation cooling. However, there are few reports on passive daytime radiation cooling of polyetheretherketone-related composite materials. In addition, studies have shown that high thermal conductivity helps heat transfer from indoor areas to outdoor areas, so materials with high thermal conductivity are generally conducive to passive cooling. Therefore, it is also necessary to improve the thermal conductivity of composite materials to enhance their application potential and utilization value. Summary of the invention

[0005] In view of this, the present invention proposes a radiation cooling and thermal conductive polyetheretherketone composite material and a preparation method and application thereof to solve the above technical problems. The obtained polyetheretherketone composite material exhibits excellent radiation cooling performance and excellent thermal conductivity.

[0006] The technical solution of the present invention is achieved in this way:

[0007] A method for preparing a radiation cooling and heat conducting polyetheretherketone composite material, the specific steps comprising:

[0008] S1, calcining boron nitride at high temperature and cooling it with the furnace to obtain hydroxyl-modified boron nitride, named HO-BN;

[0009] S2, dispersing aramid staple fibers (ANF) in a poor solvent and shearing at high speed to form microspheres, i.e. aramid fiber balls;

[0010] S3, mixing the aramid fiber balls of S2 and polyetheretherketone (PEEK) powder evenly, then adding the hydroxyl-modified boron nitride (HO-BN) of S1, and continuing to mix evenly to obtain a composite material dispersion;

[0011] S4. Melt and hot-press the composite material dispersion of S3 to obtain the target polyetheretherketone composite material, namely HO-BN&ANF / PEEK.

[0012] Furthermore, in step S1, the high temperature calcination is carried out in an atmosphere of air, at a temperature of 1000-1200°C, for a time of 4-10 hours.

[0013] Furthermore, in step S2, the poor solvent is any one of water, ethanol or acetone.

[0014] Furthermore, in step S2, the solid-to-liquid ratio of the aramid staple fiber to the poor solvent is 1:250-350 g / mL.

[0015] Furthermore, in step S2, the high-speed shearing is performed at a rotation speed of 500-1000 rpm for 10-12 hours.

[0016] Furthermore, in step S3, the mass ratio of the aramid fiber balls to the polyetheretherketone powder is 1-2:1-2.

[0017] Furthermore, in step S3, the hydroxyl-modified boron nitride accounts for 5%-50% of the total mass of the aramid fiber balls, the polyetheretherketone powder and the hydroxyl-modified boron nitride.

[0018] Furthermore, in step S4, the melt hot pressing is performed at 3-5 MPa, 345-380°C for pre-pressing for 10-15 min, and after completion, the pressure is applied to 10-30 MPa and maintained for 8-20 min.

[0019] A radiation cooling and heat conducting polyetheretherketone composite material is prepared by the above-mentioned preparation method.

[0020] A radiatively cooled, thermally conductive polyetheretherketone composite material for use in military aviation, construction, energy, and electronic packaging.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The material preparation method of the present invention is simple, and the prepared polyetheretherketone composite material exhibits excellent radiation cooling performance, thermal conductivity and thermal stability.

[0023] 2. The micro-nano structure of the aramid fiber ball of the present invention and the effective solar scattering of polyetheretherketone synergistically improve the reflective ability of the composite material. The hydroxyl-modified boron nitride can further improve the spectral selectivity of the composite material and enhance the interfacial compatibility with polyetheretherketone. At the same time, it produces hydrogen bonds with the amide bonds in the aramid fiber ball, which can strengthen the interaction between materials, reduce phonon scattering, reduce interfacial thermal resistance, and promote heat flow transmission. At the same time, the large volume of the aramid fiber ball allows the hydroxyl-modified boron nitride to form an isolation structure, construct a complete heat conduction path, and effectively improve the thermal conductivity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Infrared images of boron nitride and hydroxyl-modified boron nitride.

[0025] Figure 2 It is the thermal weight loss curve of the HO-BN&ANF / PEEK composite material of Example 1 and Examples 4-8.

[0026] Figure 3 The UV-visible reflectance spectrum images of the composite materials of Example 1 and Comparative Examples 1-2.

[0027] Figure 4 It is the infrared emissivity spectrum image of the composite material of Example 1 and Comparative Examples 1-2.

[0028] Figure 5 This is a test diagram of the cooling ability of the composite material of Example 1. DETAILED DESCRIPTION

[0029] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0030] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0031] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0032] The size of the aramid staple fiber of the present invention is 1-2 mm; the heating rate of the S1 calcination and the heating rate of the S4 melt hot pressing of the present invention are not specifically limited, and any rate familiar to those skilled in the art can be used; the mixing stirring rate in S3 is not specifically limited, and any stirring frequency familiar to those skilled in the art can be used; the poor solvent of the present invention is any one of water, ethanol or acetone.

[0033] Example 1

[0034] The preparation method of the radiation cooling and heat conducting polyetheretherketone composite material of this embodiment comprises the following specific steps:

[0035] S1. In an air atmosphere, 10 g of boron nitride was placed in a tube furnace for high-temperature calcination, specifically: the temperature was raised to 1100°C at a heating rate of 10°C / min, kept at that temperature for 6 hours, and cooled to room temperature with the furnace to obtain hydroxyl-modified boron nitride, named HO-BN;

[0036] S2, 10 g of aramid staple fiber (ANF) was dispersed in 3000 mL of acetone, sheared at 750 rpm for 11 h to form microspheres, washed, and vacuum dried at 80 °C for 12 h to obtain aramid fiber balls;

[0037] S3, weighing 5 g of aramid fiber balls and 5 g of polyetheretherketone (PEEK) powder, adding them into a three-dimensional dynamic mixer, mixing at a speed of 300 rpm for 2 h, then adding 10 g of hydroxyl-modified boron nitride (HO-BN), and continuing to mix for 1 h to obtain a composite material dispersion with a HO-BN filling amount of 50 wt%;

[0038] S4. Melt hot pressing the composite material dispersion, specifically: spread the composite material dispersion in a mold with an inner diameter of 5×5 cm, pre-press for 10 min in a molding machine at 5 MPa and 360°C, keep the temperature unchanged, pressurize to 20 MPa, apply pressure for 15 min, remove the pressure, and cool to room temperature to obtain the target polyetheretherketone composite material, i.e., 50wt% HO-BN&ANF / PEEK.

[0039] Example 2

[0040] The preparation method of the radiation cooling and heat conducting polyetheretherketone composite material of this embodiment comprises the following specific steps:

[0041] S1. In an air atmosphere, 10 g of boron nitride was placed in a tube furnace for high-temperature calcination. Specifically, the temperature was raised to 1000°C at a heating rate of 10°C / min, kept at that temperature for 4 hours, and cooled to room temperature with the furnace to obtain hydroxyl-modified boron nitride, named HO-BN.

[0042] S2, 10 g of aramid staple fiber (ANF) was dispersed in 2500 mL of acetone, sheared at a speed of 500 rpm for 10 h to form microspheres, washed, and vacuum dried at 80 ° C for 12 h to obtain aramid fiber balls;

[0043] S3, weighing 5 g of aramid fiber balls and 10 g of polyetheretherketone (PEEK) powder, adding them into a three-dimensional dynamic mixer, mixing at a speed of 300 rpm for 2 h, then adding 15 g of hydroxyl-modified boron nitride (HO-BN), and continuing to mix for 1 h to obtain a composite material dispersion with a HO-BN filling amount of 50 wt%;

[0044] S4. Melt hot pressing the composite material dispersion, specifically: spread the composite material dispersion in a mold with an inner diameter of 5×5 cm, pre-press for 15 minutes in a molding machine at 3MPa and 345°C, keep the temperature unchanged, pressurize to 10Mpa, apply pressure for 8 minutes, remove the pressure, and cool to room temperature to obtain the target polyetheretherketone composite material, i.e., 50wt% HO-BN&ANF / PEEK.

[0045] Example 3

[0046] The preparation method of the radiation cooling and heat conducting polyetheretherketone composite material of this embodiment comprises the following specific steps:

[0047] S1. In an air atmosphere, 10 g of boron nitride was placed in a tube furnace for high-temperature calcination. Specifically, the temperature was raised to 1200°C at a heating rate of 10°C / min, kept at that temperature for 10 h, and cooled to room temperature with the furnace to obtain hydroxyl-modified boron nitride, named HO-BN.

[0048] S2, 10 g of aramid staple fiber (ANF) was dispersed in 3500 mL of acetone, sheared at 1000 rpm for 12 h to form microspheres, washed, and vacuum dried at 80 ° C for 12 h to obtain aramid fiber balls;

[0049] S3, weighing 10 g of aramid fiber balls and 5 g of polyetheretherketone (PEEK) powder, adding them into a three-dimensional dynamic mixer, mixing at a speed of 300 rpm for 2 h, then adding 10 g of hydroxyl-modified boron nitride (HO-BN), and continuing to mix for 1 h to obtain a composite material dispersion with a HO-BN filling amount of 50 wt%;

[0050] S4. Melt hot pressing the composite material dispersion, specifically: spread the composite material dispersion in a mold with an inner diameter of 5×5 cm, pre-press for 15 minutes in a molding machine at 5MPa and 380°C, keep the temperature unchanged, pressurize to 30Mpa, apply pressure for 20 minutes, remove the pressure, and cool to room temperature to obtain the target polyetheretherketone composite material, i.e., 50wt% HO-BN&ANF / PEEK.

[0051] Example 4

[0052] On the basis of Example 1, the amount of hydroxyl-modified boron nitride added in step S3 was adjusted to 6.67 g, and finally 40 wt % HO-BN&ANF / PEEK was obtained.

[0053] Example 5

[0054] On the basis of Example 1, the amount of hydroxyl-modified boron nitride added in step S3 was adjusted to 4.29 g, and finally 30 wt % HO-BN&ANF / PEEK was obtained.

[0055] Example 6

[0056] On the basis of Example 1, the amount of hydroxyl-modified boron nitride added in step S3 was adjusted to 2.5 g, and finally 20 wt % HO-BN&ANF / PEEK was obtained.

[0057] Example 7

[0058] On the basis of Example 1, the amount of hydroxyl-modified boron nitride added in step S3 was adjusted to 1.1 g, and finally 10 wt% HO-BN&ANF / PEEK was obtained.

[0059] Example 8

[0060] On the basis of Example 1, the amount of hydroxyl-modified boron nitride added in step S3 was adjusted to 0.53 g, and 5 wt% HO-BN&ANF / PEEK was finally obtained.

[0061] Test Example 1

[0062] The thermal conductivity of 50wt% HO-BN&ANF / PEEK prepared in Examples 1-3 and 5wt% HO-BN&ANF / PEEK40wt% HO-BN&ANF / PEEK prepared in Examples 4-8 was tested using a thermal conductivity tester (flash method LFA467, Germany). The results are shown in Table 1.

[0063] Table 1

[0064]

[0065] It can be seen from Table 1 that the HO-BN & ANF / PEEK composite materials prepared by the preparation method of the present invention have excellent thermal conductivity, and the greater the HO-BN filling amount, the better the thermal conductivity.

[0066] Among them, see Figure 1 The infrared image shows that 814cm -1 and 1369cm -1 The infrared characteristic peak of BN bond is 3343cm -1 The broad peak appearing at is the OH absorption peak, indicating that boron nitride has been successfully modified.

[0067] Figure 2 is the thermal weight loss curve of the HO-BN&ANF / PEEK composite material of Example 1 and Examples 4-8. Figure 2 It can be seen that the temperature when the composite material loses 5% of its weight is higher than 575° C., indicating that the HO-BN&ANF / PEEK composite materials prepared in Example 1 and Examples 4-8 have good thermal stability.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that the hydroxyl-modified boron nitride is replaced by boron nitride, and the rest is the same as Example 1.

[0070] That is, the preparation method of the radiation cooling and heat conducting polyetheretherketone composite material of this comparative example comprises the following specific steps:

[0071] S1, 10g of aramid staple fiber (ANF) was dispersed in 3000mL of acetone, sheared at 750rpm for 11h to form microspheres, washed, and vacuum dried at 80℃ for 12h to obtain aramid fiber balls;

[0072] S2, weighing 5 g of aramid fiber balls and 5 g of polyetheretherketone (PEEK) powder, adding them into a three-dimensional dynamic mixer, mixing at a speed of 300 rpm for 2 h, then adding 10 g of boron nitride (BN), and continuing to mix for 1 h to obtain a composite material dispersion with a BN filling amount of 50 wt%;

[0073] S4. Melt hot pressing the composite material dispersion, specifically: spread the composite material dispersion in a mold with an inner diameter of 5×5 cm, pre-press for 10 minutes in a molding machine at 5MPa and 360°C, keep the temperature unchanged, pressurize to 20Mpa, apply pressure for 15 minutes, remove the pressure, and cool to room temperature to obtain a composite material, i.e., 50wt% BN&ANF / PEEK.

[0074] Comparative Example 2

[0075] The difference from Example 1 is that the aramid fiber balls are missing, and the rest is the same as Example 1.

[0076] That is, the preparation method of the radiation cooling and heat conducting polyetheretherketone composite material of this comparative example comprises the following specific steps:

[0077] S1. In an air atmosphere, 10 g of boron nitride was placed in a tube furnace for high-temperature calcination, specifically: the temperature was raised to 1100°C at a heating rate of 10°C / min, kept at that temperature for 6 hours, and cooled to room temperature with the furnace to obtain hydroxyl-modified boron nitride, named HO-BN;

[0078] S2, weighing 5 g of polyetheretherketone (PEEK) powder and 10 g of hydroxyl-modified boron nitride (HO-BN), adding them into a three-dimensional dynamic mixer, mixing at a speed of 300 rpm for 2 h, and obtaining a composite material dispersion with a HO-BN filling amount of 50 wt%;

[0079] S4. Melt hot pressing the composite material dispersion, specifically: spread the composite material dispersion in a mold with an inner diameter of 5×5 cm, pre-press for 10 min in a molding machine at 5 MPa and 360°C, keep the temperature unchanged, pressurize to 20 MPa, apply pressure for 15 min, remove the pressure, and cool to room temperature to obtain a composite material, i.e., 50wt% HO-BN / PEEK.

[0080] Test Example 2

[0081] The composite materials of Example 1 and Comparative Examples 1 and 2 were tested for sunlight reflection ability, infrared radiation ability and radiation cooling performance. In addition, the thermal conductivity of Comparative Examples 1 and 2 was tested using the method in Test Example 1. The results are as follows: Figure 3-5 And as shown in Table 2.

[0082] Table 2

[0083]

[0084] As can be seen from Table 2, comparative example 1 uses boron nitride, and the thermal conductivity of its composite material is reduced. This shows that the hydroxyl-modified boron nitride used in the present invention can produce hydrogen bonds with the amide bonds in the aramid fiber balls, strengthen the interaction between materials, reduce phonon scattering, reduce interfacial thermal resistance, promote heat flow transmission, and improve thermal conductivity. Comparative example 2 lacks aramid fiber balls, and the thermal conductivity of its composite material is reduced, indicating that the large volume of aramid fiber balls allows the hydroxyl-modified boron nitride to form an isolation structure, construct a complete thermal conductivity path, and improve the thermal conductivity of the composite material. This shows that the hydroxyl-modified boron nitride and aramid fiber balls synergistically enhance the thermal conductivity of the composite material.

[0085] In addition, from Figure 3 It can be seen from the UV-visible reflectivity spectrum that the average reflectivity of Example 1 is greater than that of Comparative Examples 1 and 2. Compared with Comparative Example 1, the hydroxyl-modified boron nitride in Example 1 can enhance the sunlight reflectivity of the composite material. Compared with Comparative Example 2, the micro-nano structure of the aramid fiber ball in Example 1 synergistically improves the sunlight reflectivity of the composite material.

[0086] from Figure 4 It can be seen from the infrared emissivity spectrum that in the two atmospheric windows of 3-5μm and 8-13μm, the infrared radiation capacity of Example 1 of the present invention is higher than that of Comparative Example 1 and Comparative Example 2.

[0087] from Figure 5 It can be seen from the cooling capacity test that under outdoor environmental conditions, the composite material of Example 1 of the present invention can achieve a maximum ambient temperature drop of 10.85°C, indicating that it has good radiation cooling performance.

[0088] However, the radiation cooling performance of Comparative Examples 1 and 2 is reduced.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a radiation cooling and heat conducting polyetheretherketone composite material, characterized in that: The specific steps include: S1, calcining boron nitride at high temperature and cooling it with the furnace to obtain hydroxyl-modified boron nitride; S2, dispersing the aramid staple fibers in a poor solvent and shearing them at high speed to form microspheres, i.e. aramid fiber balls; S3, mixing the aramid fiber balls of S2 and the polyetheretherketone powder evenly, then adding the hydroxyl-modified boron nitride of S1, and continuing to mix evenly to obtain a composite material dispersion; S4. Melt and hot-press the composite material dispersion of S3 to obtain the target polyetheretherketone composite material.

2. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S1, the high temperature calcination atmosphere is air, the temperature is 1000-1200°C, and the time is 4-10 hours.

3. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S2, the poor solvent is any one of water, ethanol or acetone.

4. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S2, the solid-to-liquid ratio of the aramid staple fiber to the poor solvent is 1:250-350 g / mL.

5. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S2, the high-speed shearing is performed at a rotation speed of 500-1000 rpm for 10-12 hours.

6. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S3, the mass ratio of the aramid fiber balls to the polyetheretherketone powder is 1-2:1-2.

7. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S3, the hydroxyl-modified boron nitride accounts for 5%-50% of the total mass of the aramid fiber balls, the polyetheretherketone powder and the hydroxyl-modified boron nitride.

8. The method for preparing a radiation cooling and heat conducting polyetheretherketone composite material according to claim 1, characterized in that: In step S4, the melt hot pressing is performed at 3-5 MPa, 345-380°C for pre-pressing for 10-15 min, and after completion, the pressure is applied to 10-30 MPa and maintained for 8-20 min.

9. A radiation cooling and heat conducting polyetheretherketone composite material, prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the radiation cooling and heat conducting polyetheretherketone composite material according to claim 9 in the fields of military aviation, construction, energy and electronic packaging.

Citation Information

Patent Citations

  • SEBS-SnO2 composite film for radiation cooling and preparation process of SEBS-SnO2 composite film

    CN118727269A

  • Thermal-conductive and wear-resistant composite material with metallic luster

    CN109553921A

  • Short glass fiber reinforced polyether-ether-ketone resin-based composite material

    CN117327370A

  • Radiation sheilding composition and method for preparing the same

    KR1020160142634A

  • Corona-resistant plastic-based composite material and preparation method therefor, corona-resistant composite sheet, and stator of electric motor

    WO2024141111A1

Cited By

  • Polyether-ether-ketone composite membrane as well as preparation method and application thereof

    CN120348044A

  • Ultralow-temperature-resistant PAEK composite material and preparation method thereof

    CN120590775A